Surface and Interface Engineering of Zn Anodes in Aqueous Rechargeable Zn‐Ion Batteries - Zheng, Jiaxian; Huang, Zihao; Ming, Fangwang; Zeng, Ye; Wei, Binbin; Jiang, Qiu; Qi, Zhengbing; Wang, Zhoucheng; Liang, Hanfeng (Small (Weinheim an der Bergstrasse, Germany), 2022)
Rechargeable zinc‐ion batteries (ZIBs) have shown great potential as an alternative to lithium‐ion batteries. The ZIBs utilize Zn metal as the anode, which possesses many advantages such as low cost, high safety, eco‐friendliness, and high capacity. However, on the other hand, the Zn anode also suffers from many issues, including dendritic growth, corrosion, and passivation. These issues are largely related to the surface and interface properties of the Zn anode. Many efforts have therefore been devoted to the modification of the Zn anode, aiming to eliminate the above‐mentioned problems. This review gives a comprehensive summary on the mechanism behind these issues as well as the recent progress on Zn anode modification with focus on the strategies of surface and interface engineering, covering the design and application of both the Zn anode supports and surface protective layers, along with abundant examples. In addition, the promising research directions and perspective on these strategies are also presented. Zn anodes in aqueous Zn‐ion batteries suffer from dendritic growth, corrosion, and passivation issues. A comprehensive review of the recent progress in Zn anode modification with focus on the design and application of both Zn anode supports and surface protective layers is presented. Additionally, promising research directions are also suggested to promote the development of highly reversible Zn anodes.